The Influence of Organizational Commitment on The Community Participation at Meat Tourism Village Toba Samosir North Sumatera - Erika Revida, Badaruddin, Sukarman Purba (International Journal of Advanced Science and Technology, 2020)
The general objective of this study was to analyze the influence of organizational commitment on the community participation at Meat Tourism Village Toba Samosir, North Sumatera. The particular objective were to analyze affective commitments, continuance commitment and normative commitment on the community participation at Meat tourism village Toba Samosir, North Sumatera. The sample of this research were 50 peoples (head of family) who live at Meat Tourism Village Toba Samosir, North Sumatera. Data collection techniques carried out by documentation studies, research instruments, interviews and observations. The data analysis technique used by multiple regression analysis techniques. The results of the study indicated that there was a positive and significant influence between organizational commitments on the community participation. There was a positive and significant influence between affective commitments on the community participation. There was a positive and significant influence between continuance commitment on the community participation, and there was a positive and significant influence between normative commitment on the community participation at Meat tourism village Toba Samosir, North Sumatera. The suggestions proposed in this study need to increase the role of religious leaders and community leaders by providing communication, information and education about the importance of normative, affective and continuous commitment so that the community participation will be increase at Meat Tourism Village Toba Samosir North Sumatera